2019
DOI: 10.1002/bio.3747
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of europium‐ and titanium‐doped Y2O3 nanoparticles

Abstract: Luminescent nanoparticles of Y 2 O 3 doped with europium (Eu) and/or titanium (Ti) were synthesized using modified sol-gel routes. The crystalline cubic phase was confirmed using X-ray powder diffraction (XRD). Particle morphology and size were evaluated using scanning and transmission electron microscopy. High-resolution transmission electron microscopy showed that the synthesis method affected the average particle size and the Fourier transform of the images showed the lattice plane distances, indicating tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…[68] Chen et al [69] investigated the relationship between the Xray excited PersL of Sr 2 MgSi 2 O 7 : Eu 2 + , Dy 3 + and the temperature, reaction pH, Eu/Dy ratio, and calcination time through this method, providing an optimization strategy for the practical application of phosphors. Teixeira et al [70] reported Eu 3 + , Ti 3 + / Ti 4 + co-doped Y 2 O 3 nanoparticles by coconut water-based solgel method and the obtained nanomaterials with particle size of 30~100 nm. Strong and PersL of Eu 3 + can be realized by effective energy transfer from Ti 3 + /Ti 4 + to Eu 3 + .…”
Section: Sol-gel Methodsmentioning
confidence: 99%
“…[68] Chen et al [69] investigated the relationship between the Xray excited PersL of Sr 2 MgSi 2 O 7 : Eu 2 + , Dy 3 + and the temperature, reaction pH, Eu/Dy ratio, and calcination time through this method, providing an optimization strategy for the practical application of phosphors. Teixeira et al [70] reported Eu 3 + , Ti 3 + / Ti 4 + co-doped Y 2 O 3 nanoparticles by coconut water-based solgel method and the obtained nanomaterials with particle size of 30~100 nm. Strong and PersL of Eu 3 + can be realized by effective energy transfer from Ti 3 + /Ti 4 + to Eu 3 + .…”
Section: Sol-gel Methodsmentioning
confidence: 99%